2014
DOI: 10.3171/2014.5.jns132244
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for sylvian fissure arteriovenous malformations with emphasis on hemorrhage risks and seizure outcomes

Abstract: Object Sylvian fissure arteriovenous malformations (AVMs) present substantial management challenges because of the critical adjacent blood vessels and functional brain. The authors investigated the outcomes, especially hemorrhage and seizure activity, after stereotactic radiosurgery (SRS) of AVMs within or adjacent to the sylvian fissure. Methods This retrospective single-institution analysis examined the authors' experiences with Gamma Knife surgery for AVMs of the sylvian fissure in cases treated from 1987 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…The rates of seizure improvement were 29% at 3 years, 36% at 5 years, 50% at 10 years, and 60% at 15 years. In that study, the rate of improved seizure control was higher for patients with 3 10. incomplete obliteration (p = 0.042), lower among patients with a history of prior hemorrhage, and higher for patients with small nidus diameter (< 2 cm). In comparison to the current study, seizures may be more difficult to control and may have different prognosticating factors (obliteration, hemorrhage, and nidus size) in patients with sylvian fissure seizures.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The rates of seizure improvement were 29% at 3 years, 36% at 5 years, 50% at 10 years, and 60% at 15 years. In that study, the rate of improved seizure control was higher for patients with 3 10. incomplete obliteration (p = 0.042), lower among patients with a history of prior hemorrhage, and higher for patients with small nidus diameter (< 2 cm). In comparison to the current study, seizures may be more difficult to control and may have different prognosticating factors (obliteration, hemorrhage, and nidus size) in patients with sylvian fissure seizures.…”
Section: Discussionmentioning
confidence: 71%
“…Bowden et al studied 87 patients who underwent SRS for AVMs of the sylvian fissure. 3 Of these, 36 patients experienced seizures before SRS. The risk for pre-SRS seizures was lower for younger patients and for patients with a history of previous intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that a prior hemorrhage tended to lead to less successful headache management of AVM patients. This type of negative impact on symptom resolution in patients with a hemorrhagic AVM has been illustrated also in patients with seizures …”
Section: Discussionmentioning
confidence: 79%
“…This type of negative impact on symptom resolution in patients with a hemorrhagic AVM has been illustrated also in patients with seizures. 23,24 Study Limitations.-There are inevitable limitations of this study, the most pronounced being the impact of recall bias, which can significantly impact headache reporting and subsequently can result in an increased margin of error. The natural waxing and waning of migraine symptoms may have significant impact on our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Improvement or cure from the epilepsy is a desirable additional therapeutic effect. The results in terms of Engel class I outcomes depend on a number of factors such as anatomical location, size, and age of patient but is in the order of 53% -66% [16,17]. However the median time to seizure free status is in the order of 20 months, again reflecting the late radiation effects on tissue [16].…”
Section: Stereotactic Radiotherapy In the Management Of Epilepsymentioning
confidence: 99%